2021
DOI: 10.3390/ijerph18126632
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Musculoskeletal Disorders among Secondary Schoolteachers in Hail, Saudi Arabia: A Cross-Sectional Survey

Abstract: Musculoskeletal disorders (MSDs) are one of the most common occupational health hazards and serious health concerns among teachers. About 39% to 95% of teachers suffer from musculoskeletal pain that can lead to a decline in their performance, frequent sick leaves and early retirement, and can have a negative impact on their quality of life. The aim of this study was to investigate the prevalence of and risk factors for MSDs among secondary schoolteachers in Hail, Saudi Arabia. A cross-sectional study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
28
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 34 publications
12
28
2
2
Order By: Relevance
“…Our findings suggested that female workers are more likely to develop WMSD symptoms in the shoulders area, which is in line with many published works in the literature [ 30 , 31 , 32 ]. Treaster et al [ 33 ] suggested that the tasks of female workers are usually characterized by a high static loading of the shoulders area, requiring precision and the repetitive use of small muscles, which may account for the higher prevalence of WMSDs in the shoulders of female workers.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings suggested that female workers are more likely to develop WMSD symptoms in the shoulders area, which is in line with many published works in the literature [ 30 , 31 , 32 ]. Treaster et al [ 33 ] suggested that the tasks of female workers are usually characterized by a high static loading of the shoulders area, requiring precision and the repetitive use of small muscles, which may account for the higher prevalence of WMSDs in the shoulders of female workers.…”
Section: Discussionsupporting
confidence: 92%
“…This prevalence is also similar to that reported in previous studies among teachers in Estonia (66.7%) [ 36 ], Delhi, India (65.1%) [ 37 ], Saudi Arabia, Al-Jouf Region (68.5%) [ 24 ] and Saudi Arabia, Abha region (62.5%) [ 38 ]. It is lower than that was reported among teachers in Bolivia (86%) [ 17 ], Machakos, Kenya (85.1%) [ 39 ], Fiji (88.9%) [ 40 ], Nigeria (70.2%) [ 33 ], Hail, Saudi Arabia (87.3%) [ 25 ] and Chile (88.9%) [ 41 ]. However, it is higher in comparison with that reported among teachers in Brazil (55%) [ 1 ], Turkey ((51.4%) [ 8 ], (36%) [ 42 ]) and Terengganu, Malaysia (40.1%) [ 43 ].…”
Section: Discussionmentioning
confidence: 71%
“…Comparisons were made to ensure same phrasing and meaning of the questions by the researchers. The NMQ was also translated into Arabic and used in previous Saudi Arabian studies [ 11 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Korábbi tanulmányok eredményei szerint a tanárok mintegy 25-95%-a szenved izom-és csontrendszeri fájdalomtól, ami teljesítményromláshoz, gyakori betegszabadsághoz vezet, és negatívan befolyásolja életminőségüket. A mozgásszervi problémák legmagasabb arányban a nyak, a váll és a derék területén alakulnak ki, általában több régiót érintve (Althomali, Amin, Alghamdi, & Shaik, 2021;Ojukwu et al, 2021;Vega-Fernández, Lera, Leyton, Cortés, & Lizana, 2021;Elias, Downing, & Mwangi, 2019;Kebede, Abebe, Woldie, & Yenit, 2019;Solis-Soto, Schön, Solis-Soto, Parra, & Radon, 2017;Zamri, Moy, & Hoe, 2017;Karakaya, Karakaya, Tunç, & Kıhtır, 2015;Ceballos & Santos, 2015;Yue, Liu, & Li, 2012;Dilek & Ilker, 2012;Erick & Smith, 2011). A mozgásszervi elváltozások megjelenése tekintetében differenciáló tényezőnek bizonyul az iskola típusa és földrajzi elhelyezkedése.…”
Section: Bevezetésunclassified
“…Elsődlegesen azonosított kockázati tényezőnek számít a tanári pályán eltöltött idő (Ojukwu et al, 2021;Kebede et al, 2019;Mohseni Bandpei et al, 2014;Erick & Smith, 2011), az életkor (Ojukwu et al, 2021;Amit & Malabarbas, 2020;Ceballos & Santos, 2015;Mohseni Bandpei et al, 2014), a női nem (Althomali et al, 2021;Elias et al, 2019;Kebede et al, 2019;Ceballos & Santos, 2015;Karakaya et al, 2015;Erick & Smith, 2011), a magasabb testtömegindex (Vega-Fernández et al, 2021;Kraemer, Moreira & Guimarães, 2020;Mohseni Bandpei et al, 2014), a dohányzás (Althomali et al, 2021), az alacsonyabb fizetési csoportba való tartozás (Amit & Malabarbas, 2020), a munkahelyi pszichoszociális tényezők (Elias et al, 2019;Zamri et al, 2017;Ceballos & Santos, 2015;Mohseni Bandpei et al, 2014) és az alacsony vezetői támogatás (Elias et al, 2019). A mozgásszervi elváltozások a testi panaszok megjelenése mellett negatív hatást gyakorolnak az életminőségre (Vega-Fernández et al, 2021), illetve kedvezőtlenül befolyásolják az általános egészségérzetet (Karakaya et al, 2015;Dilek & Ilker, 2012), a mentális egészséget (Vega-Fernández et al, 2021;Ceballos & Santos, 2015), továbbá együttjárást mutatnak a szorongással (Zamri et al, 2017), a depresszióval (Dilek & Ilker, 2012) és az alvászavarral (Kebede et al, 2019).…”
Section: Bevezetésunclassified